Open-water swimming - Bradford, C. D.; Gerrard, D. F.; Cotter, J. D. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
Open-water swimming (OWS) is undertaken in diverse bodies of water and climatic locations, over distances mostly between 1.5 and 88 km. OWS provides a unique and potentially hazardous thermoregulatory challenge for multiple reasons, but the lack of information on physiological, performance and health effects is conspicuous and surprising. At least one heat-related death and numerous cold-related deaths provide sobering testament to these challenges. Net effects are difficult to predict because of large and typically opposing influences of the exercise medium, temperature, posture, arm-based mode and the individual differences in fitness and anthropometry. For example, evaporative power is essentially nullified but is counteracted by the high convective power of water immersion. Immersion and exercise have opposing effects on blood volume but dehydration-induced hypovolaemia will typically develop for physical, physiological and practical reasons. Competition between metabolic and thermoregulatory demands for cardiac output is lessened by the posture, immersion effects and location of active musculature, but increased by the reliance on convective heat loss. Behavioural thermoregulation may be more important than in terrestrial exercise but concomitantly impaired for practical and potentially also physiological (thermo-afferent) reasons. This chapter addresses such issues and provides resultant advice on potential countermeasures including those discussed in detail but generic contexts in preceding chapters.